2014
DOI: 10.1177/0022034514552493
|View full text |Cite
|
Sign up to set email alerts
|

Denture Wearing during Sleep Doubles the Risk of Pneumonia in the Very Elderly

Abstract: Poor oral health and hygiene are increasingly recognized as major risk factors for pneumonia among the elderly. To identify modifiable oral health–related risk factors, we prospectively investigated associations between a constellation of oral health behaviors and incident pneumonia in the community-living very elderly (i.e., 85 years of age or older). At baseline, 524 randomly selected seniors (228 men and 296 women; mean age, 87.8 years) were examined for oral health status and oral hygiene behaviors as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
2
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 27 publications
3
126
2
8
Order By: Relevance
“…On the other hand, a negative effect of biocompatibility might counteract this effect due to a higher surface roughness. Accumulation of oral biofilm is a highly relevant risk factor in geriatric populations 28) , where the presence of oral bacteria may cause aspiration pneumonia 29) , especially when the dentures are worn during the night 30) . At this stage, a better or worse biocompatibility of the novel prepolymerized denture resins remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a negative effect of biocompatibility might counteract this effect due to a higher surface roughness. Accumulation of oral biofilm is a highly relevant risk factor in geriatric populations 28) , where the presence of oral bacteria may cause aspiration pneumonia 29) , especially when the dentures are worn during the night 30) . At this stage, a better or worse biocompatibility of the novel prepolymerized denture resins remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited research in this area, mixed infection with P. gingivalis and T. denticola in a mouse model of aspiration pneumonia has been shown to cause considerably higher inflammatory responses, impaired bacterial clearance and more severe lung pathology compared with single infection with either bacterium 142 . Importantly, the control of the oral microbial burden substantially decreases the incidence of aspiration pneumonia in frail elderly people 143,144 , which suggests a direct association between oral bacteria and lung pathology in susceptible individuals. These results warrant more basic studies to understand the mechanisms involved.…”
Section: Periodontitis and Respiratory Diseasesmentioning
confidence: 99%
“…Sjøgren et al suggested that 10% of nursing-home deaths from aspiration pneumonia could be avoided by improving oral hygiene 21 . Wearing dentures at night is likewise associated with oral infections, high microbial load, and increased incidence of pneumonia 22 . Hence addressing neglected oral hygiene can become a major pre-occupation for elders dependent on care.…”
Section: Oral Health In Old Agementioning
confidence: 99%